Outcomes of Endoscopic Transcanal Same Sitting Bilateral Myringoplasty: An Observational Study in a Tertiary Care Center - Tulachan, Bishow; Acharya, Roshan (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION The trend of same sitting bilateral myringoplasty has been sparkling the Otolaryngologists interest to go either microscopically or endoscopically as per the surgeon’s skill and comfort as unilateral myringoplasty would lead to considerable increase in operation cost, time and discomfort to the patient. MATERIAL AND METHODS This prospective, observational study was held in the Department of Otorhinolaryngology and Head and Neck Surgery (ORL-HNS), Universal College of Medical Sciences-Teaching Hospital (UCMS-TH). There were 30 patients with age range of 8-50 years. All cases were done under general as well as local anesthesia. Tragal cartilage and the temporalis fascia graft were used as a graft material. Graft uptake results were assessed after 12 weeks and the intraoperative and postoperative complications were observed. RESULTS 12 (40%) were male and 18 (60%) female. 15 (50%) patients had temporalis fascia graft and other 15 (50%) patients had tragal cartilage graft. 1 patient in each (fascia/cartilage) had a residual peroration in the subsequent operated side. The graft uptake success rate was 96.7% in both the temporalis fascia graft and the tragal cartilage graft myringoplasties with statistically signiﬁcant association between type of graft and outcome (p=0.976. There were no signiﬁcant complications observed during the 3 months follow up except the discomfort due to the bilateral mastoid dressing. CONCLUSION It is a safe, minimally invasive, and satisfactory procedure with a favourable and similar graft uptake success rate with the advantages of cost reduction, single anesthesia exposure, a low rate of postoperative complications and better cosmesis.